Empirical Likelihood for Partial Parameters in ARMA Models with Infinite Variance - Jinyu Li; Wei Liang; Shuyuan He (Journal of Applied Mathematics)
This paper proposes a profile empirical likelihood for the partial parameters in ARMA(p,q) models with infinite variance. We introduce a smoothed empirical log-likelihood ratio statistic. Also, the paper proves a nonparametric version of Wilks’s theorem. Furthermore, we conduct a simulation to illustrate the performance of the proposed method.